A crucial process: organic matrix and magnesium ion control of amorphous calcium carbonate crystallization on β-chitin film. Issue 1 (15th October 2014) - Ma, Yufei; Feng, Qingling
Abstract : ACC transformation processes occurring on chitin film mediated by a water soluble matrix or magnesium ions in aqueous solution were investigated. Abstract : Amorphous calcium carbonate (ACC) particles with a diameter of about 300 nm were synthesized first. Then the as-prepared products were used to investigate the ACC transformation processes occurring on chitin film under the control of a water soluble matrix (WSM, extracted from aragonite pearls, China) or magnesium ions in aqueous solution. Raman spectroscopy, transmission electron microscopy (TEM) together with selected area electron diffraction (SAED) and field-emission scanning electron microscopy (FE-SEM) equipped with energy-dispersive X-ray (EDX) were used to characterize the crystallized calcium carbonate from ACC. The results demonstrate that the existence of a WSM and chitin film offers the ability to control the pure aragonite phase, leading to the formation of rod-like aragonite crystal aggregates. Comparatively, the collaborative effect of magnesium ions and chitin film not only induces the formation of the aragonite crystal aggregates, but also inhibits the transformation from ACC to Mg-calcite. Moreover, a possible transformation mechanism has been proposed and discussed.